2019
DOI: 10.1038/s41598-019-44228-w
|View full text |Cite
|
Sign up to set email alerts
|

Latent Infection of Valsa mali in the Seeds, Seedlings and Twigs of Crabapple and Apple Trees is a Potential Inoculum Source of Valsa Canker

Abstract: A real-time quantitative PCR assay using a species-specific primer pair was developed to rapidly and accurately quantify Valsa mali , the causative pathogen of apple Valsa canker (AVC), in crabapple seeds, crabapple seedlings, apple twigs and apple seeds. Surveys were conducted in different regions, and crabapple or apple seeds were collected for V . mali detection by qPCR assay. Our results showed that 12.87% to 49.01% of crabapple seeds col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…mali and Valsa mali affect apple trees by infecting the leaves and young shoots and subsequently causing defoliation, which leads to premature fruit drop [29][30][31][32] . A number of studies have characterized genes important for the resistance of apple to drought and pathogens and have examined their potential use in the breeding of resistant apple [33][34][35][36][37] . MYB88 and MYB124 and their homologous genes in apple participate in the response to salt, cold, and drought stress 1,2,[38][39][40][41] .…”
Section: Introductionmentioning
confidence: 99%
“…mali and Valsa mali affect apple trees by infecting the leaves and young shoots and subsequently causing defoliation, which leads to premature fruit drop [29][30][31][32] . A number of studies have characterized genes important for the resistance of apple to drought and pathogens and have examined their potential use in the breeding of resistant apple [33][34][35][36][37] . MYB88 and MYB124 and their homologous genes in apple participate in the response to salt, cold, and drought stress 1,2,[38][39][40][41] .…”
Section: Introductionmentioning
confidence: 99%
“…Infected hyphae develop inter-and intra-cellularly and penetrate extensively into the phloem and xylem of trunks and main crotches (Tamura and Saito 1982;Ke et al 2013), leading to perennial infections which cannot be effectively controlled through chemical treatments or surgical removes (Abe et al 2007). Moreover, recent studies have indicated that infection can be asymptomatic (Zang et al 2012;Zhang et al 2018), and latent infections in seeds, seedlings and twigs provide a potential inoculum source for the disease (Meng et al 2019). Although numerous management approaches, including physical, chemical and biological methods, have been implemented to limit the disease, apple Valsa canker remains prevalent in many apple production areas (Peng et al 2016).…”
Section: Symptom Infection and Damagementioning
confidence: 99%
“…At the scale of the population level, the adaptive potential of the pathogen may reflect the effects of climate change [78], causing greater potential damage to trees [49]. Crabapple, the rootstocks of apple trees, has been identified along with apple seeds and seedlings as a potential inoculum source [79], which makes the control procedures of AVC more difficult. Therefore, to reduce the spread of V. mali, it is of vital importance to limit latent sources of infection: improving garden management methods to cultivate vigorous trees [3], coating new pruning wounds with protection film [4], and using special pruning tools for special gardens, as well as strengthening the management of diseased trees.…”
Section: The Role Of Environmental Variables In Effecting the Distribution Of V Mali And Corresponding Strategies For Preventing Avcmentioning
confidence: 99%